Bioethics, public moral argument, and social responsibility - King, Nancy M. P.; Hyde, Michael J., 1950- (New York : Routledge, 2012)
'Bioethics, Public Moral Argument, and Social Responsibility explores the role of democratically oriented argument in promoting public understanding and discussion of the benefits and burdens of biotechnological progress. The contributors examine moral and policy controversies surrounding biomedical technologies and their place in American society, beginning with an examination of discourse and moral authority in democracy, and addressing a set of issues that include: dignity in health care; the social responsibilities of scientists, journalists, and scholars; and the language of genetics and moral responsibility. Much discussion of biotechnological advances rests on the rights of individuals to make autonomous choices and on societal decisions not to interfere with willing buyers and sellers. But intensifying democratic debates about key issues like health insurance reform and genetic research have begun to broaden our public vision, to include awareness of cost, a sense of collective responsibility to help others, and the need to work together to set limits we can live with. In scholarly journals, newspapers, magazines, on television, radio, and hundreds of web sites, public moral argument about the benefits and burdens of biotechnology is ubiquitous. Science and society have thus created an increasingly fragmented discourse, which we need to examine together. The book's authors, experts from the sciences and humanities, step beyond their disciplinary boundaries to assume the ethical responsibility of translating their expertise into forms that help promote fruitful public conversation.'--
Includes bibliographical references and index.
Keywords: Medical ethics -- Philosophy; Bioethics -- Philosophy; Biotechnology -- Philosophy